HUBUNGAN ANTARA PENGETAHUAN DAN DUKUNGAN KELUARGA DALAM PENGOBATAN TB PARU DI PUSKESMAS SASAK KABUPATEN PASAMAN BARAT - Novita " Erina; Bayhakki " "; Yulia Irvani Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract This study aims to determine the relationship between knowledge and support of the family in the treatment of pulmonary tuberculosis in Puskesmas Sasak Kabupaten Pasaman. This research used descriptive research design correlation with cross sectional approach. Number of samples was 46 samples taken using consecutive sampling. Measuring instrument used was a questionnaire with 28 statements that have been tested its validity and reliability. The analysis used was a univariate analysis distribution frequency test and bivariate with Chi-square test. The results showed that there was a significant relationship between knowledge and support of the family in the treatment of pulmonary tuberculosis in Puskesmas Sasak Kabupaten Pasaman with p-value = 0.000 where p-value < alpha (p-value <0.05). Based on these results, it is expected the patient and the family to follow advice and methods for treatment and adhere to treatment for 6 months or as recommended by health workers so that can decrease prevalence of pulmonary TB incidence rates. Keywords: Family support, Knowledge, Pulmonary tuberculosis.